2017
DOI: 10.1016/j.aap.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind distracted driving behavior: The role of age and executive function in the engagement of distracted driving

Abstract: Performing secondary tasks, such as texting while driving, is associated with an increased risk of motor vehicle collisions (MVCs). While cognitive processes, such as executive function, are involved in driving, little is known about the relationship between executive control and willingness to engage in distracted driving. This study investigated the relationship between age, behavioral manifestations of executive function, and self-reported distracted driving behaviors. Executive difficulty (assessed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 43 publications
5
40
0
Order By: Relevance
“…The TWD group showed higher levels of impulsivity than the Non-TWD group, although the difference was statistically significant only for the BIS. These results are consistent with previous research (Pope et al, 2017) and support a general conclusion that drivers with lower levels of executive function and higher levels of impulsivity are more likely to text while driving.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The TWD group showed higher levels of impulsivity than the Non-TWD group, although the difference was statistically significant only for the BIS. These results are consistent with previous research (Pope et al, 2017) and support a general conclusion that drivers with lower levels of executive function and higher levels of impulsivity are more likely to text while driving.…”
Section: Discussionsupporting
confidence: 92%
“…Despite its potential significance, a relation between executive function and texting while driving has received little empirical attention. One notable exception is Pope et al (2017), in which lower levels of executive function were related to a higher frequency of distracted driving in young, middle age and older drivers. It is important to note, however, that Pope et al (2017) averaged data from multiple behaviors (e.g., drinking, eating, talking, using a GPS, and texting) and employed a general index of distracted driving as a dependent variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have also revealed that distracted driving is a phenomenon seen across age groups. Furthermore, the findings have revealed that middle-aged adults engaged in distracted driving behaviors just as frequently as young adults [61]. Preventive action is needed, but it would be necessary to develop a multi-factor model.…”
Section: Driver Distraction In Croatiamentioning
confidence: 99%
“…To date, the relationship between executive control, age, and distracted driving has been under-researched. To address this, research focused on these parameters by collecting detailed information on weekly engagement in distracted driving behaviors from 59 participants (Pope et al, 2016). The operators ranged from young, middle, and older adults who self-reported executive difficulty as well as demographic information.…”
Section: Driver Characteristicsmentioning
confidence: 99%